Free-gap evaluation for two-lane rural highways - António Lobo (2011)
Studies related to operating speed predicting models' development require vehicles' speed under free-flow conditions to be collected at different sites. Thus, a critical issue is the definition of the gap (or headway) from which the speed of one vehicle is not affected by the speed of the vehicle ahead. In many studies, a 5-s headway was adopted as the reference headway value from which a vehicle could be assumed to travel at a free-flow speed. Justifications for this value's application are not clearly presented in the literature, and some authors suggest the use of other reference values. This paper presents a definition for platoon from observed values of vehicles' time gap. The reference gap value between two successive vehicles considered as traveling in a nonplatoon condition is defined as "free gap." A five-step methodology is described and tested for road conditions in Portugal. The application performed showed both the adequacy of the methodology proposed and the convenience of exploratory studies aimed at the identification of platoon gap (or headway) suitable for specific operating speed studies. According to the methodology proposed, a 6-s gap is a suitable reference for future data collection on operating speed on Portuguese roads. This result suggests the need to review the headway reference values found in the literature for representing free-flow general conditions.